Correlation analysis of serum AAG/LDH and BLa levels with the prognosis of severe pneumonia complicated with shock: Serum AAG/LDH and BLa levels in severe pneumonia with shock - Yang, Jie; Li, Jia; Tang, Feng; Wu, Mengjuan; Wang, Zhiqiang; Song, Ziqi (Journal of Medical Biochemistry, 2026)
Objective This study aimed to explore the relationships between serum α1-acid glycoprotein (AAG), lactate dehydrogenase (LDH), and blood lactate (BLa) levels and the severity and prognosis of severe pneumonia (SP) complicated with shock in elderly patients to provide useful references for clinical diagnosis and treatment.Methods From May 2024 to July 2025, 364 elderly patients with SP combined with shock who were admitted to our hospital composed the SP combined with shock group. Depending on their severity, the patients were split into low-, medium-, and high-risk groupings. A good prognosis group and a bad prognosis group were subsequently assigned to the patients based on the follow-up data. An additional 364 elderly patients with SP who did not experience shock and were admitted to our hospital during that time frame were chosen to be part of the SP group. Following measurements of each research participant's serum levels of AAG, LDH, and BLa, the AAG/LDH ratio was calculated. APACHE II (Acute Physiology and Chronic Health Evaluation II) and CPIS (clinical pulmonary infection) scores, and the AAG, LDH, and BLa levels of elderly patients with SP combined with shock were correlated with each other using Spearman correlation analysis. Using multivariate logistic regression analysis, the factors influencing the progression to high risk and poor prognosis in elderly patients with SP accompanied with shock were investigated. A receiver operating characteristic (ROC) curve was used to assess the predictive power of serum AAG/LDH and BLa for the prognosis of elderly individuals with SP accompanied with shock.Results While the SP group's serum LDH level was lower than the SP group's, the SP combined with shock group's serum AAG and BLa levels and AAG/LDH ratios were higher. Each of these variations was statistically significant (P
Keywords: Severe pneumonia; Shock; α1-acid glycoprotein; Lactate dehydrogenase; Blood lactate; APACHE II score